On the genus acrospirifer Helmbrecht et Wedekind, 1923 (Brachiopoda, Lower Devonian) (Contributions to Lower Devonian brachiopods from the Rheinisches Schiefergebirge and adjacent areas, 1) - Jansen,U. (Journal of the Czech Geological Society, 2001)
Numerous Devonian spiriferid species with strongly plicate shells distributed almost worldwide have been assigned to the taxon Acrospirifer Helmbrecht et Wedekind, 1923. In order to prepare a revised diagnosis for the genus, materials of the type species A. primaevus (Steininger, 1853) from its regio typica (Rheinisches Schiefergebirge, Germany) are redescribed. Well-preserved specimens display a fimbriate micro-ornamentation, with minute spines along the margins of concentric growth lamellae. This observation contradicts the diagnosis of the genus published by Gourvennec (1989) and the diagnosis of the family Acrospiriferidae Termier et Termier, 1949 published by Carter et al. (1994); both diagnosis include as a main character a capillate micro-ornamentation lacking minute spines. Due to the new observations, the diagnosis of the genus Acrospirifer is revised. The taxonomic position of different species up to now assigned to the genus is discussed. According to the present knowledge, Acrospirifer is restricted to its type species probably only occurring in the Ardenno-Rhenish Mountains (? southern England, ? Czech Republic). In the Lower Devonian of West Europe and North Africa purely capillate forms are abundant which have hitherto been determined as Acrospirifer; Gourvennec's diagnosis was also based on these forms. They do not belong to Acrospirifer but to the genus Filispirifer Jansen, 2001 comprising the group of "Spirifer" fallax Giebel, 1858. This group also occurs in the Lower Emsian Erbsloch-Grauwacke and in Hercynian Limestones (Kellerwald and Harz Mountains, Germany). It is concluded that previous determinations of Acrospirifer or even A. primaevus in West Europe and North Africa should be reconsidered, and also stratigraphical alignments based on these determinations. At last, the family Acrospiriferidae can hardly be maintained in its present definition.
Keywords: Brachiopoda; Spiriferida; Palaeozoic; Lower Devonian; stratigraphy; Rheinisches Schiefergebirge; Germany